The effects of increasing running speed on vGRF and asymmetry - Hierholzer, K. M. (East Tennessee State University, 2021)
Biomechanical and physiological parameters related to running performance are usually studied separately. However, evaluating both aspects together could be beneficial in improving athletic performance. The purpose of this study was to observe the change in peak vGRF and asymmetry as speed increases, while observing physiological responses during a O2maxtest. Data from athlete monitoring of 12 cross-country and triathlon athletes were analyzed. The athlete monitoring protocol included three unweighted countermovement jumps and a O2maxtest performed by the athletes. The athletes had an average O2maxof 53.4 ± 7.7 mL/kg/min, while their average vGRF asymmetry throughout the O2maxtestwas 1.38 ± 0.68%. A strong, positive correlation was found between average vGRF and average blood lactate (r=0.93), indicating that as vGRF increased so did blood lactate. It was concluded that physiological and biomechanical parameters are related in athletic performance. Therefore, athlete monitoring should include analysis of both physiological and biomechanical parameters in order to form a more well-rounded analysis of athlete performance.